Peran Strategis Tes dan Pengukuran dalam Meningkatkan Akurasi Evaluasi Kinerja Fisik - Tori Siahaan; Cristian Siregar; Ahmad Hidayat; Vebrianto Purba; Mesnan; Mawardinur (SPRINTER: Jurnal Ilmu Olahraga, 2026)
Physical performance evaluation is a crucial component in the world of sports, aiming to objectively assess individual fitness. This study aims to analyze the strategic role of tests and measurements in improving the accuracy of physical performance evaluation through a literature review approach. The method used is a literature study by reviewing various scientific sources, including national and international journals, as well as related books. The results of the study indicate that tests and measurements play a crucial role in generating objective data, especially when supported by valid and reliable instruments. Furthermore, the use of standardized tests can improve the quality of evaluation and support decision-making in training programs. In conclusion, tests and measurements are key components in an accurate and scientifically based physical performance evaluation system.